Penataan Ruangan di Perpustakaan Umum Kota Solok - Anugrah, Dexa; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
Abstract This study to describe the interior design of Solok Public Library, as aÂ result in the optimal interior design. Data collection tool that is used to describe the qualitative data to the library is direct observation, interviews with staff Solok Public Library, and literature. The analysis of data in descriptive. Based on analyzing the data, it was concluded that the interior design of Solok Public Library is not optimal. Because Solok Public Library does not attention aspects of the interior design library. Keywords: interior design; design library Â